Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.jpcb.6b01497
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Heme Ruffling Changes in MhuD Using UV–vis Spectroscopy

Abstract: For decades it has been known that an out-of-plane ruffling distortion of heme perturbs its UV-vis absorption (Abs) spectrum, but whether increased ruffling induces a red or blue shift of the Soret band has remained a topic of debate. This debate has been resolved by the spectroscopic and computational characterization of Mycobacterium tuberculosis MhuD presented here, an enzyme that converts heme, oxygen, and reducing equivalents to nonheme iron and mycobilin. W66F and W66A MhuD have been characterized using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
138
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(149 citation statements)
references
References 48 publications
(145 reference statements)
10
138
1
Order By: Relevance
“…Whereas the mean out-of-plane deviation for TPFPP diphenylcarbene was 1.03 Å (SI Appendix, Table S2), it is smaller for carbene-bound Rma TDE (0.6 Å; the deviation for Rma TDE alone is 0.7 Å). The difference in distortion between both Rma TDE structures is small, and both values are within the range reported for c-type cytochrome proteins (0.3-1.2 Å) (30). Ruffling is known to be the main distortion in these proteins and is thought to be induced by covalent attachment of the heme to the protein (31).…”
Section: Significancesupporting
confidence: 81%
“…Whereas the mean out-of-plane deviation for TPFPP diphenylcarbene was 1.03 Å (SI Appendix, Table S2), it is smaller for carbene-bound Rma TDE (0.6 Å; the deviation for Rma TDE alone is 0.7 Å). The difference in distortion between both Rma TDE structures is small, and both values are within the range reported for c-type cytochrome proteins (0.3-1.2 Å) (30). Ruffling is known to be the main distortion in these proteins and is thought to be induced by covalent attachment of the heme to the protein (31).…”
Section: Significancesupporting
confidence: 81%
“…While the changes in the ν 10 marker band are broadly consistent with the changes in the NMR and EPR data, with a lower energy observed for more ruffled protein variants, the changes in this band are on the order of only a few cm −1 , while NMR and EPR spectra show significantly greater changes. We also note that UV-Vis absorption data also have been implemented as a probe of ruffling, but large changes in ruffling are required to see any shift in absorption bands [62].…”
Section: Spectroscopic Probes Of Heme Rufflingmentioning
confidence: 99%
“…A prominent example of a protein that hosts a dynamic haem is Mycobacterium tuberculosis MhuD. [10][11][12] MhuD is a non-canonical haem oxygenase (HO) whose haem substrate undergoes a dynamic ruffling deformation, but it has not yet been ascertained whether the substrate dynamics have a functional role.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic measurements have shown that the large ruffling deformation observed in the X-ray crystal structure of cyanide-inhibited MhuD (MhuD-haem-CN, PDB ID 4NL5) arises from a dynamic haem substrate that is present in solution as an equilibrium mixture of planar and ruffled haem. [10][11][12] One explanation for the presence of two haem conformations in MhuD is that it is a consequence of the fact that at least four polypeptide conformational states exist. 10,13,14 Alternatively, from a haem electronic structure viewpoint, the ruffled conformation can be attributed to a hidden pseudo Jahn-Teller distortion arising from vibronic coupling of the 2 B2g and 2 A2u excited states of the planar species by a b1u vibration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation